Typical Facial Lesions: A Window of Suspicion for Progressive Disseminated Histoplasmosis—A Case of Asian Prototype - Prasan K. Panda; Siddharth Jain; Rita Sood; Rajni Yadav; Naval K. Vikram (Case Reports in Infectious Diseases)
Histoplasmosis is caused by a dimorphic fungus Histoplasma capsulatum in endemic areas, mainly America, Africa, and Asia. In India, it is being reported from most states; however, it is endemic along the Ganges belt. We report a case of an apparently immunocompetent male who presented with 3-month history of fever, cough, and weight loss with recent onset odynophagia and had hepatosplenomegaly and mucocutaneous lesions over the face. The differential diagnosis of leishmaniasis, tuberculosis, leprosy, fungal infection, lymphoproliferative malignancy, and other granulomatous disorders was considered, but he succumbed to his illness. Antemortem skin biopsy and bone marrow aspiration along with postmortem liver, lung, and spleen biopsy showed disseminated histoplasmosis. This case highlights the need for an early suspicion of progressive disseminated histoplasmosis in the presence of classical mucocutaneous lesions even in an immunocompetent patient suffering from a febrile illness. Cure rate approaches almost 100% with early treatment, whereas it is universally fatal if left untreated.